Relación entre los precios en alojamientos y restaurantes con la cantidad de arribos a hoteles de Loreto: 2010 – 2020 - Saavedra Torres, Nicole (2023)
The objective of this study is to determine the degree of correlation between prices in lodging and restaurants and the number of hotel arrivals in Loreto during the period 2010 to 2020. It also seeks to delimit the variation of prices in lodging and restaurants in Loreto during the period 2010 to 2020. Determine the variation in the number of hotel arrivals in Loreto during the period 2010 to 2020. The present research is quantitative because it will be based on the collection and analysis of numerical data. It is a non-experimental design in that the data will be taken from a pre-existing base, without experimentation or variation in the variables. Its type of design will be longitudinal since a study will be carried out in the time interval from 2010 to 2020. It will be correlational in scope because it will measure the degree of relationship between two variables, the independent variable being the number of hotel arrivals and the dependent variable the prices of accommodations and restaurants.